Lower back pain scale and return to sports in elite Taekwondo athletes with lower back injuries - Jung, Tae Gyeom; Park, Ki Jun (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2023)
Objectives This study compares back pain scale, functionality, and ability to return to sport according to sex for Taekwondo athletes with lower back injuries.Methods The study included 52 elite adolescent Taekwondo athletes (26 in both male and female groups), who participated in advanced competitions at a training camp between January and December 2021. The lower back pain scale, Modified Oswestry Disability Index, isokinetic muscular function, and recovery time according to sex were assessed using an independent sample t-test. Pearson's correlation and simple linear regression analyses were used to evaluate the correlation between variables, and identify factors associated with pain.Results The lower back pain scale (p=0.003) and recovery time (p=0.018) significantly differed between the sexes. In all athletes, the pain scale was significantly correlated with the Modified Oswestry Disability Index (p<0.001) and recovery time (p<0.001). For each point increase in the pain scale, the Modified Oswestry Disability Index increased by 3.01 (p=0.001) and 3.25 (p=0.013) for males and females, respectively. In addition, recovery time increased by 1.70 days (p<0.001) and 1.98 days (p<0.001) in males and females, respectively.Conclusion These results may help generate the data needed to develop rehabilitation programs that improve an athlete’s performance.Ziele Diese Studie vergleicht die Skala der Rückenschmerzen, die Funktionalität und die Fähigkeit, zum Sport zurückzukehren, nach Geschlecht für Taekwondo-Athleten mit Verletzungen des unteren Rückens.Methoden Die Studie umfasste 52 jugendliche Elite-Taekwondo-Athleten (26 in männlichen und weiblichen Gruppen), die zwischen Januar und Dezember 2021 an fortgeschrittenen Wettkämpfen in einem Trainingslager teilnahmen. und Erholungszeit nach Geschlecht wurden mit einem unabhängigen Stichproben-t-Test bewertet. Pearsons Korrelation und einfache lineare Regressionsanalysen wurden verwendet, um die Korrelation zwischen Variablen zu bewerten und mit Schmerz verbundene Faktoren zu identifizieren.Ergebnisse Die Schmerzskala im unteren Rückenbereich (p=0,003) und die Erholungszeit (p=0,018) unterschieden sich signifikant zwischen den Geschlechtern. Bei allen Athleten korrelierte die Schmerzskala signifikant mit dem Modified Oswestry Disability Index (p<0,001) und der Erholungszeit (p<0,001). Für jeden Punktanstieg auf der Schmerzskala stieg der Modified Oswestry Disability Index um 3,01 (p=0,001) und 3,25 (p=0,013) für Männer bzw. Frauen. Darüber hinaus verlängerte sich die Erholungszeit um 1,70 Tage (p<0,001) bzw. 1,98 Tage (p<0,001) bei Männern und Frauen.Schlussfolgerung Diese Ergebnisse können dazu beitragen, die Daten zu generieren, die für die Entwicklung von Rehabilitationsprogrammen erforderlich sind, die die Leistung eines Athleten verbessern.
Keywords: Taekwondo; sports injury; pain scale; back pain; return to sports